Answer:
Last Option A – (x, y) = A' (x + 3, y + 1)
Explanation:
Step one: Write the transformation coordinates.
In the figure above point A shows the transformed form of A I.e. A' (x', y') will represent A' (-1, 5) while coordinate (x, y) represents A (-4, 4).
Step Two: find the relationship between A and A'
Using substitution let's find the relationship between (x, y) and (x', y')
x' = -1 = (-4 + 3) = (x + 3)
y' = 5 = 4 + 1 = (y + 1)
Therefore A(x, y) → A'(x + 3, y + 1)
Option D is the correct option.